TOTAL WRIST ARTHRODESIS EFFICIENCY IN VARIOUS UPPER LIMB ORTHOPEDIC PATHOLOGIES - Tymoshenko, Serhii; Kotova, Maria (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Wrist arthrodesis for different pathologies has important specific features and yields varying functional outcomes. Objective. Based on the analysis of functional parameters dynamics to assess the total wrist arthrodesis efficacy for different upper limb pathologies. Methods. An analysis was performed on the dynamics of cylindrical grip strength and upper limb disability (qDASH score) before and one year after total wrist arthrodesis in 49 patients with various conditions, including wrist osteoarthritis, chronic brachial plexus injuries, distal radius giant cell tumor, rheumatoid arthritis, and wartime wrist joint injuries. Results.Wrist arthrodesis improved cylindrical grip strength in patients with degenerative wrist osteoarthritis by a median of 14 kg (range: 7–15 kg; IQR: 1 kg), in tumors by a median of 10 kg (range: 8–11 kg; IQR: 1,5 kg), and in consequences of wartime injuries involving joint surface defects by a median of 4 kg (range: 2–39 kg; IQR: 3 kg). In cases of rheumatoid arthritis, the median improvement was 3,4 kg (range: 2–9 kg; IQR: 2 kg). Effectiveness was minimal in patients with chronic brachial plexus injuries. The greatest reduction in upper limb disability (qDASH score) was observed in patients with of wartime wrist trauma consequences, with a median improvement of 40 points (range: 0–68 points; IQR: 27 points). In wrist osteoarthritis, the median improvement was 20 points (range: 9–39 points; IQR: 9 points), while relatively minor improvements were noted in patients with tumors, rheumatoid arthritis, and brachial plexus injuries. Total wrist arthrodesis is an effective surgical procedure; however, depending on the pathology, the indications, surgical conditions, techniques, and outcomes differ significantly and are notably varied.